THE TEACHING OF MATHEMATICS TO STUDENTS WITH INTELLECTUAL DISABILITIES: A TEACHERS CONCEPTION - Costa, Ailton Barcelos da (2018)
Mathematical skills are important to provide an autonomous life to people. However, learning mathematics has been a challenge for children in general, including children with deficiency. This research investigated the perception of teachers when teaching math to students with intellectual disabilities. The data collection was made through a questionnaire to 32 math teachers via social network and e-mail. The analysis of data was carried out qualitatively by categorizing responses in five classes. The results showed the need for teachers to have more information on how to deal with this public through initial or continuing education. The impacts of this lack of information is evidenced through the teachers’ fear of including students with intellectual disabilities in the mainstream education and difficult in accessing and preparing mathematics teaching materials for these students. Keywords: Intellectual disability. Mathematics teaching. Teachers’ conception.